強力反応点(灸点、禁灸点)のもつ電気特性の検討 - 井手, 亮; 渡邉, 勝之; 早水, 丈治 (人体科学, 2013)
We set out to investigate the differences in electrical characteristics of strongly reactive points including a moxibustion point and a point contraindicated for moxibustion. Methods: 1) We evaluated the electric potential of the skin surface at each measurement point, including strongly reactive points. 2) We measured the resistance between two strongly reactive points before and after changing the direction of the electric current applied with an external voltage. Results: 1) The measured electric potential of the skin surface was highest for the electro-dermal point, diminishing in the order of point contraindicated for moxibustion, moxibustion point, acupoint, and control point. 2) With the electric current flowing from the moxibustion point, the resistance was lower than with the current flowing in the other direction. Conclusion: The point contraindicated for moxibustion had higher electric potential than the moxibustion point. The electric potential of the skin surface is caused by abnormalities in the body and reflects the degree of influence that interventions can have on the skin surface. The two strongly reactive points differed in the electric potential of the skin surface, and this difference affected the load voltage. When the electric current flowed between two strongly reactive points, the resistance value differed.